Formal Verification of Restoring Dividers made Fast and Simple - Dasari, Jiteshri; Ciesielski, Maciej (2023 60th ACM/IEEE Design Automation Conference (DAC), 2023)
The paper describes a formal verification method for hardware implementation of restoring divider circuits. The method is based on setting select signals to predefined constants to reduce the design to easily verifiable circuit components, followed by their verification using standard equivalence checking and SAT. It is then concluded by a global proof that the composition of those components indeed implements a divider. In contrast to previous approaches, the verification is done on a functional level without any reverse engineering of the internal structure. The results show significant improvement in verification time compared to other methods. The proposed approach can also be used in debugging by localizing the source of a bug. This feature is currently not available in the existing verification tools and will be a subject of future work.